La Revista de Psiquiatría y Disciplinas Conexas y los inicios del psicoanálisis en el Perú: una nota - León, Ramón (1985)
The author, continuing a series of studies that are being published in this journal, analyzes the relationship between the development of the Revista de Psiquiatría y Disciplinas Conexas and the introduction of the psychoanalytic ideas in Perú and Latín America.